2013
DOI: 10.1021/mz400556q
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Gold-Nanoparticle Assemblies with Tunable Interparticle Distances Mediated by Multifunctional RAFT Polymers

Abstract: A strategy for the controlled assembly of gold nanocrystals into dispersed three-dimensional superstructures is presented. A multifunctional RAFT agent was used to prepare multiblock polystyrene (4.4−17.8 kDa) with trithiocarbonate groups as junctions between the individual blocks. Addition of these polymers to two-phase Brust−Schiffrin gold nanoparticles (4.1 nm) resulted in the formation of stable gold-nanoparticle assemblies dispersed in toluene. TEM analysis revealed that the interparticle distances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 34 publications
2
48
0
5
Order By: Relevance
“…[10] He found that controlled structures are formed, when multiblock oligomers were employed in the functionalization. [11] By the degree of oligomerization, the spatial distances in the produced colloidal superparticles [12][13][14] can be fine-tuned.…”
Section: Grafting Of Multifunctional Raft Agents To Brust-schiffrin Amentioning
confidence: 99%
See 1 more Smart Citation
“…[10] He found that controlled structures are formed, when multiblock oligomers were employed in the functionalization. [11] By the degree of oligomerization, the spatial distances in the produced colloidal superparticles [12][13][14] can be fine-tuned.…”
Section: Grafting Of Multifunctional Raft Agents To Brust-schiffrin Amentioning
confidence: 99%
“…In order to quantify this kind of evaluation, the position of the maximum V max,SEC and the full width at half maximum w SEC of the signals are listed for all examined nanohybrid samples in Table 8 11 . This shows that all nanoparticles are well separated from each other and are not interconnected by the multiblock polymers.…”
Section: Tab 84mentioning
confidence: 99%
“…Recently, hybrid nanoparticles composed of an inorganic core and an organic polymer shell have received considerable attention as a new class of nanoscale materials [1][2][3][4][5]. The hybrid nanoparticles have held a significant promise in the areas of sensing, catalysis, and biomedical applications [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Verbindung 2 wurde analog zu einer kürzlich beschriebenen Methode [18] synthetisiert, und die Struktur von 2 wurde durch NMR-Spektroskopie bestätigt (Abbildungen S1 und S2). RAFT-Agens 1 [13] wurde verwendet, um PN i PAAM mit linearer Topologie zu erhalten. Sämtliche Polymerproben wurden durch dreifaches Ausfällen gereinigt und mittels Grçßenausschlusschromato- [19] In vorangegangenen Studien konnten wir Korrekturfaktoren für verschiedene Sternpolymere (darunter solche mit vier Armen), die mittels einer gegen lineare Standards geeichten SEC-Anlage analysiert wurden, bestimmen.…”
unclassified
“…(Abbildung S6 zeigt eine exemplarische TEMAufnahme, Abbildung S7 die Durchmesserhistogramme für beide Partikelsorten, welche keine Überlappung zeigen). TOAB kann leicht durch konkurrierende Liganden verdrängt werden, [13,21] was eine geringe Bindungsstärke von TOAB zu Gold und daraus folgende mangelnde kolloidale Stabilität impliziert. Deshalb wurde 10 Minuten nach Zugabe der BSPartikel lineares PNiPAAM hinzugefügt, um die Außenseiten der Satellit-Partikel, die vom zentralen Planet-Partikel abgewandt sind, zu stabilisieren.…”
unclassified